The Efficacy of Different Chemotherapy Regimens for Advanced Biliary Tract Cancer: A Systematic Review and Network Meta-Analysis - Li, Yan; Zhou, Yaoyao; Hong, Yonglan; He, Meizhi; Wei, Shuyi; Yang, Chen; Zheng, Dayong; Liu, Feiye (Frontiers in Oncology, 2019)
Background: Although gemcitabine plus cisplatin (GP) is considered as standard chemotherapy for patients with advanced biliary tract cancer (BTC), the optimal regimen remains unknown. Methods: Using Network meta-analysis (NMA), a systematic review was conducted to find the most effective chemotherapy regimen for advanced BTC. We searched PubMed, Web of Science, Embase, Scopus and the Cochrane Library for articles published before October 6, 2018. Articles about chemotherapeutic comparisons were included. Hazard ratios (HRs) for overall survival (OS) and progression free survival (PFS) were estimated while odd ratios (ORs) was assessed for objective response rate (ORR). Results: The NMA included 25 studies and 3,312 individuals. Among all the regimens, Folfox-4 regimen obtained a superior difference in OS (BSC vs. Folfox-4, HR 3.4, 95% CI 1.7-6.7). XP was slightly better than GP in OS and GS approximately obtained the same efficacy to GP (HR for XP vs. GP 0.74, 95% CI 0.51-1.1; HR for GS vs. GP 1.1, 95% CI 0.71-1.5). Most of the targeted therapies included in this study tend to achieve better in PFS and ORR but failed to improve OS, in which E-GEMOX achieved the best ORR when compared to BSC (OR 0.03, 95% CI 0.00-0.94). Conclusions: Folfox-4 regimen is likely to be the optimal chemotherapy for patients with advanced BTC and the predominant targeted therapy haven’t achieved significant success currently. XP and GS can be considered as alternatives for advanced BTC.